(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2023)
Antibiotics are chemicals that prevent or eliminate bacterial growth and are widely used in various applications. They were first discovered by Alexander Fleming in 1928 when he noticed that a mold called Penicillium notatum inhibited the growth of Staphylococcus aureus bacteria. Since then, antibiotics have been extensively studied and utilized to combat bacterial infections.There are several potential sources of antibiotic-producing microorganisms, including soil, water, plants, animals, and even fermented foods. Actinomycetes, a type of bacteria commonly found in soil, are known for their ability to produce a wide range of antibiotics. Marine environments are also considered a rich source of antibiotic-producing microorganisms.The production of antibiotics by bacteria is of great interest, as it offers the potential for the development of new natural product-based drugs. Actinomycetes, particularly Streptomyces species, have been a major focus of antibiotic research and have yielded thousands of distinct secondary metabolites, many of which are antibiotics.Antibiotics play various natural functions in microbial interactions in different environments. They can act as weapons or shields, protecting bacteria from predators or competing microbes. Antibiotics can also have concentration-dependent effects, acting as inhibitors at high concentrations and mediators of intracellular signaling at low concentrations.The production of antibiotics by bacteria in soil and plant-associated environments has been extensively studied. Bacterial genera such as Bacillus, Pseudomonas, and Streptomyces have been found to produce bioactive peptides with antimicrobial properties. These antibiotics can help bacteria survive in harsh environments by inhibiting the growth of predators or competitors.